Development of Education and Economic Circulation in Supporting Local Potential as Community Empowerment Efforts Amid the Covid-19 Pandemic - Sukmawati, Desi; Maryanti, Rina (Universitas Pendidikan Indonesia (UPI), 2021)
The development of education and economic circulation has an important role in encouraging economic growth based on community empowerment amid the Covid-19 pandemic. The purpose of this research is to see and develop education and economic circulation in supporting local potential as an effort to empower the community amid the Covid-19 pandemic. This study used a type of descriptive research with a combined research method approach. We also used methods in the process of developing the local potential of the economic community through human literacy and digital literacy to encourage the development of social media in communicating as an effort to prevent and handle Covid-19.Â The importance of education can be found, such as digital literacy and human literacy to be able to improve information literacy skills in the field of economics. The subjects of this study were businesses from the community as well as institutions in the UP2K (Family Income Improvement Effort) program. The results of this study showed that the Real Work Lecture program in the community can improve community interaction to carry out empowerment monitoring in the development of local potential as a recovery in the economic field.